The triple helix effect on innovation performance - Luengo, María Jesús (2013)
Innovation is related to the growth of economies and companies, and in a changing environment, like the present, it is introduced as a fundamental means for competitive advantage. This study aims at analyzing the relation between the companies’ capacity for innovation and obtaining the same information by means of cooperation with competitors, suppliers, universities and public institutions (Triple Helix). First, we developed a literature review on related concepts and, then, by using the structural equation method, we elaborated a model to respond to and accept the hypothesis proposed, which highlights the relation between the innovative performance of companies and the information obtained from the Triple Helix. The survey was conducted with a sample of Spanish companies researched by the National Institute of Statistics (INE) from 2008 to 2010.